An option approach to water delegation - Ephraim A. Clark; Gérard Mondello (Fondazione Eni Enrico Mattei (FEEM), 1997)
The problem that we address in this paper stems from the trend to delegation in the water management field. The problem that we address refers to the municipality's negotiating disadvantage in the face of some cartelized water management. We discuss the specific characteristics of the delegation auction that render it useless as a tool for collective welfare maximisation. We show that the remaining tool for achieving collective welfare maximisation, i.e. the municipality's right to revoke delegation and return to direct management, is also ineffective due to a lack of credibility that is essentially financial in nature. Thus, if the credibility of revocation could be restored, the municipality's bargaining power could also be restored. Using standard methods of stochastic calculus, we model the municipality's right of revocation as a call option held by the municipality. We show that the value of this option depends to a large extent on the exercise price, which is partly determined by objective economic criteria and partly by legal and institutional conventions. Based on this we suggest that credibility could be restored by the constitution of a fund at least as large as the effective exercise price.
Keywords: Q25; O33; G13; 330; Delegation; Water management; Auctions and bids; Wasserversorgung; Auktionstheorie; Theorie